Development of an Interactive E-Module on the History of Quantum Physics Assisted by Flip PDF Professional - Anggita Dewi Mithasari; Silvia Laeli; Muhamad Mi’da Farkhan; Rida Siti Nur’aini Mahmudah (Postgraduate, University of Mataram, 2024)
The rapid development of technology greatly affects the education system in Indonesia, especially in the use of Information Technology (IT) devices such as hardware and software in the teaching and learning process. This research focuses on developing interactive e-modules using the Flip PDF Professional application to improve students' quantum physics learning experience. This research problem addresses the difficulties faced by students in understanding quantum physics concepts, which leads to low academic achievement. This study aims to assess the feasibility and user satisfaction of the interactive e-module